Endothelial Progenitor Cells of the Human Placenta and Fetoplacental Circulation: A Potential Link to Fetal, Neonatal, and Long-term Health - Gumina, Diane L.; Su, Emily J. (Frontiers in Pediatrics, 2017)
The fetoplacental circulation plays a key role in both short- and long-term outcomes, and aberrant flow indices as manifested by abnormal fetal Doppler velocimetry within this compartment have been associated with significant adverse consequences. These include fetal growth restriction, which often coexists with preeclampsia, and long-lasting medical issues as a result of both the underlying pathology and prematurity such as bronchopulmonary dysplasia, chronic lung disease, and neurodevelopmental delay. Furthermore, it is also clear that exposure to an abnormal in utero environment increases risk for long-term, adulthood issues such as cardiovascular disease. Endothelial progenitor cells (EPCs) have been implicated in vasculogenesis and angiogenesis, and they have been isolated from both human placenta and umbilical cord blood. This review outlines the extensive nomenclature of EPCs, summarizes existing literature surrounding human placental and umbilical cord blood EPCs, explores their potential role in pregnancy complications and adverse perinatal outcome, and highlights key areas where future investigations are needed.